2020
DOI: 10.1093/her/cyaa038
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of constructs related to dissemination and implementation of an early childhood systems-level intervention

Abstract: Obesity and overweight in early childhood have detrimental impacts on children’s health and development. Changing policy, system and environmental features focused on physical activity and healthy eating behaviors as part of health promotion interventions can play a key role in prevention strategies in early childhood education settings. These types of changes can have broad reach and are often sustained over time, which allows for impact on children who enter the early childhood education setting year after y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Childcare directors accept a Cooperative Planning process because it helps the team improve the ways in which it promotes the planning and implementation of PA opportunities based on the childcare center’s specific needs and preferences. This confirms the findings of a recent exploratory study that identified the adaptability or flexibility of a program to meet the needs of the specific childcare center as an important dissemination and implementation factor ( Farewell et al ., 2020 ). The adaptability of an intervention, defined as ‘the degree to which an intervention can be adapted, tailored, refined, or reinvented to meet local needs’, is also described in the CFIR as an intervention characteristic facilitating the implementation ( Damschroder et al , 2009 ).…”
Section: Discussionsupporting
confidence: 89%
“…Childcare directors accept a Cooperative Planning process because it helps the team improve the ways in which it promotes the planning and implementation of PA opportunities based on the childcare center’s specific needs and preferences. This confirms the findings of a recent exploratory study that identified the adaptability or flexibility of a program to meet the needs of the specific childcare center as an important dissemination and implementation factor ( Farewell et al ., 2020 ). The adaptability of an intervention, defined as ‘the degree to which an intervention can be adapted, tailored, refined, or reinvented to meet local needs’, is also described in the CFIR as an intervention characteristic facilitating the implementation ( Damschroder et al , 2009 ).…”
Section: Discussionsupporting
confidence: 89%
“…Variation in frequency of themes between centers was not analyzed due to the small sample size included in this study. In-depth qualitative methods and associated findings are presented in a prior manuscript (Farewell et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…As factors including guideline complexity, guideline organisation/evidence credibility and action-ability of / the guidelines tend to in uence attitudes and knowledge of guidelines, dissemination strategies that target these factors have the potential to increase intentions to adopt recommendations in the ECEC setting (21,22). Despite this, there is an absence of evidence regarding the most effective dissemination strategies, with most studies relying on passive, non-targeted provision of information to communicate policy changes in ECEC settings (17,20).…”
Section: Introductionmentioning
confidence: 99%
“…As factors including guideline complexity, guideline organisation/evidence credibility and action-ability of / the guidelines tend to in uence attitudes and knowledge of guidelines, dissemination strategies that target these factors have the potential to increase intentions to adopt recommendations in the ECEC setting (21,22). Despite this, there is an absence of evidence regarding the most effective dissemination strategies, with most studies relying on passive, non-targeted provision of information to communicate policy changes in ECEC settings (17,20).With the emergence of COVID-19 and rapidly changing health and social contexts, the importance of understanding how to quickly disseminate guideline recommendations to ECEC services in a resource-e cient and time-effective manner was identi ed, and provided an opportunity to assess the impact of strategies to disseminate health-related information to the sector.As such, the aim of this 3-arm randomised controlled trial was to examine the use of different types of dissemination strategies: i) an e-newsletter; and ii) an animated video resource, compared with the provision of a standard email (passive diffusion), to assess the impact on increasing ECEC service intentions to adopt an indoor-outdoor program for the full day and offer more time outdoors. The e-newsletter and animated video formats were chosen as the dissemination resources as both are easily distributed via email, at scale, and are delivered via the same modality (email) as the control message.…”
mentioning
confidence: 99%